Analisis Vegetasi Gulma Di Pertanaman Padi (Oryza sativa) Desa Wanasari Kecamatan Semendawai Timur Kabupaten Oku Timur - Suarjaya, I Gede Arya; Rosanti, Dewi; Mutiara, Dian; Kartika, Trimin (Indobiosains, 2025)
Research of Analysis of Weeds in Rice Plantations (Oryza sativa) was conducted in April - June 2025, located in Wanasari Village, Semendawai Timur District, East OKU Regency. The purpose of the study was to analyze weed vegetation in rice plantations (Oryza sativa). This study uses survey methods. Sampling using on the plot which is carried out based on a rectangular plot measuring 2 m x 2 m with a total of 5 plots is placed systematically. The results of the study found 9 species from 7 genera and 7 families. The nine species are Scoparia dulcis, Ophiopogon japonicus, Ludwigia peploides, Ludwugia octovalvis, Ageratum conyzoides, Fimbristilys littoralis, Cyperus kyllingia, Cynodon dactylon, and Sida rhombifolia. The highest weed density calculation was in the Cynodon dactylon species with a value of 7.8 ind/m2 and the lowest in the Scoporia dulcius species with a value of 2.65 ind/m2. The highest important value index (INP) was Cynodon dactylon with an important value index value of 25.73%. While the lowest important value index was the Scoparia dulcis weed type with an important value index of 16.08%. Diversity index is included in the moderate category with a value of  2,13.